Pengaruh Isometric Handgrip Exercises Terhadap Perubahan Tekanan Darah Pada Penderita Hipertensi: Literatur Review - Sari, Adjeng Pradita; Muhlisin, Abi (Universitas Pahlawan Tuanku Tambusai, 2024)
Hypertension is better known as the silent killer which is usually interpreted as hypertension which causes death without any symptoms. Physical activity that helps sufferers to lower blood pressure is by doing isometric handgrip exercises. The study aims is to analyze and identify changes in blood pressure during isometric handgrip exercises. The method used is Literature Review. The database used to search for this article is Science Direct, PubMed, and Google Scholar which were published in 2013-2023. The keywords used were